Sudut Pandang Penulis Berita BBC Terhadap Perilaku Prabowo: Penilaian Sikap Analisis - Yolanda, Chornelia Chelsa; Riris Mutiara Paulina Simamora (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2024)
This research investigates how international media portray Prabowo's image, due to his personal branding during the election process, which has garnered public attention. Prabowo, a former military general with a controversial past, has been dubbed 'cuddly grandpa' by the youth. This study aims to analyze the attitude of BBC News authors towards Prabowo using Martin & White (2005) language appraisal analysis, specifically focusing on the attitude subsystems of affect, judgment, and appreciation. A qualitative descriptive approach was employed, the researcher gathering the data from BBC News articles discussing the Indonesian election from February to March 2024. Nine relevant articles were identified on this platform. The researchers transcribed the data into word form and utilized the AntConc corpus software to identify sentences that contains the word ‘Prabowo,’ then the researchers categorized each sentence into attitude subsystem affect, judgment, and appreciation. The findings reveal that